Project Performance Analysis Using Earned Value Management Method in Telecommunication - Widiningrum, Adelia; Pratami, Devi; Haryono, Imam (International Journal of Integrated Engineering, 2020)
One of telecommunication project in Indonesia is shut downing the obsolete telecommunication infrastructure such as Sentral Telephone Otomate in Tanjungsari Bandung. This project is a modernization project of fiber optic network for 334 locations in Tanjungsari Sub-district. To compare actual performance of the scope, schedule and cost with planning for making right decisions in project's status and performance, required controlling by using Earned Value Management method since it can integrate these three things at the same time. Status and index of project performance on the 22nd day indicate that project was behind schedule that caused loss revenue of Rp 2,600,000.00 with 98% of delays from planning and project get 94% of overruns budget from issued value with amount of Rp 7,410,000.00. In addition, forecasting is done as a corrective action of past project status and performance. It is estimated that the project duration to complete work is 31 days with total cost for the remaining work (EAC) of Rp. 140,170,00.00 from previous project performance. It is also estimated that cost for remaining work until the project is completed or ETC is Rp. 7,770,000.00 with size of the project's forecasting status is a deficit from VAC value that calculated about (Rp 7,410,000.00) and the project will complete based on the TCPI forecasting calculation.